No shortage of good days - Gierach, John, 1946- (Simon & Schuster, 2011)
A collection of fly-fishing essays reflects the author's visits to regions ranging from the Smokies and eastern Tennessee to the Canadian Maritimes and Mexico, where he explored such topics as fishing etiquette, mosquitoes, and the charms of third-rate streams.